2015
DOI: 10.1016/j.nedt.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the complexities of nursing students' feedback on the clinical learning environment: A mixed methods approach

Abstract: Although the study found overall satisfaction with clinical placement, the lower satisfaction reported by students in health-related employment, and the mixed findings regarding language spoken and satisfaction, warrant further attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 26 publications
6
28
0
3
Order By: Relevance
“…Furthermore, the clinical placement experience impacted positively on students' attitude towards people with mental illness, which corroborated with previous findings on the positive impact of mental health clinical placement on nursing students (Dawood 2012) and occupational therapy students (Gilbert & Strong 2000). Students' satisfaction with the community-based AOD rehabilitation setting in our study, as indicated by the mean CLEI-19 scale score of 69.19, is equivalent to the mean score of 69.94 reported in a previous study (Salamonson et al 2015).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, the clinical placement experience impacted positively on students' attitude towards people with mental illness, which corroborated with previous findings on the positive impact of mental health clinical placement on nursing students (Dawood 2012) and occupational therapy students (Gilbert & Strong 2000). Students' satisfaction with the community-based AOD rehabilitation setting in our study, as indicated by the mean CLEI-19 scale score of 69.19, is equivalent to the mean score of 69.94 reported in a previous study (Salamonson et al 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Students’ satisfaction with the community‐based AOD rehabilitation setting in our study, as indicated by the mean CLEI‐19 scale score of 69.19, is equivalent to the mean score of 69.94 reported in a previous study (Salamonson et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…While a skilled facilitator should provide debrief that is inclusive and safe, encouraging active learning, in reality it is difficult to achieve and relies on individual skill and capacity to work with complex groups and situations. It has been recognised in the past that clinical facilitators are often poorly prepared for the role and have varied capacity to deliver learning opportunities (Salamonson et al., ). Our findings support the need to ensure clinical facilitators are prepared and supported to achieve high levels of competency in the area of debrief, including addressing any violence that has been experienced.…”
Section: Discussionmentioning
confidence: 99%
“…Upgrades in practice accreditation reflect advanced clinical experience and practical training. Salamonson et al () found that clinical experience affects nurses' satisfaction. Our study uniquely demonstrates that upgrades in practice accreditation positively contribute to outcome expectations and career interest.…”
Section: Discussionmentioning
confidence: 99%
“…Academic programmes provide a holistic, theory‐based approach to knowledge, skills and ability development, and thus may contribute to job satisfaction (Suliman & Aljezawi, ). Clinical placement experience associated with these academic programmes provides an immediate context in which to apply these higher‐order skills and, in so doing, can improve the satisfaction of nursing students (Salamonson et al, ). Cumulatively, the knowledge, skills, abilities and experience gained through the pursuit of additional academic qualifications can provide nurses with a higher level of professional competence than in the past, and positively impact students' career choices (Halcomb et al, ).…”
Section: Introductionmentioning
confidence: 99%